Chemical bonding in copper-based transparent conducting oxides: CuMO(2) (M = In, Ga, Sc) - SCANLON, DAVID; ALLEN, JEREMY; WATSON, GRAEME WILLIAM; GODINHO, KATHERINE GITANJALI (Institute of Physics, 2011)
The geometry and electronic structure of copper-based p-type delafossite transparent conducting oxides, CuMO(2) (M = In, Ga, Sc), are studied using the generalized gradient approximation (GGA) corrected for on-site Coulomb interactions (GGA + U). The bonding and valence band compositions of these materials are investigated, and the origins of changes in the valence band features between group 3 and group 13 cations are discussed. Analysis of the effective masses at the valence and conduction band edge explains the experimentally reported conductivity trends.
PUBLISHED
Keywords: Condensed matter physics; thin films; DENSITY-FUNCTIONAL THEORY; PULSED-LASER DEPOSITION